2015
DOI: 10.1016/j.immuni.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Fap2 Protein of Fusobacterium nucleatum to Human Inhibitory Receptor TIGIT Protects Tumors from Immune Cell Attack

Abstract: SUMMARY Bacteria, such as Fusobacterium nucleatum, are present in the tumor microenvironment. However, the immunological consequences of intra-tumoral bacteria remain unclear. Here, we have shown that natural killer (NK) cell killing of various tumors is inhibited in the presence of various F. nucleatum strains. Our data support that this F. nucleatum-mediated inhibition is mediated by human, but not by mouse TIGIT, an inhibitory receptor present on all human NK cells and on various T cells. Using a library of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
854
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 1,004 publications
(872 citation statements)
references
References 32 publications
12
854
0
6
Order By: Relevance
“…Pioneering work by the Han lab utilized the animal model (described above) to demonstrate that the protein FadA is required for F. nucleatum localization to and proliferation in the placenta and its subsequent invasion into amniotic fluid and fetal tissue (Ikegami et al 2009). More recently, the adhesin Fap2 has also been shown to be important for bacterial interactions with host carbohydrates, immunomodulation and colonization of the placenta following bloodstream administration (Kaplan et al 2010;Coppenhagen-Glazer et al 2015;Gur et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work by the Han lab utilized the animal model (described above) to demonstrate that the protein FadA is required for F. nucleatum localization to and proliferation in the placenta and its subsequent invasion into amniotic fluid and fetal tissue (Ikegami et al 2009). More recently, the adhesin Fap2 has also been shown to be important for bacterial interactions with host carbohydrates, immunomodulation and colonization of the placenta following bloodstream administration (Kaplan et al 2010;Coppenhagen-Glazer et al 2015;Gur et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…N atural killer cells are lymphocytes of the innate immune system, which specialize in the eradication of tumor cells and cells infected with viruses or bacteria (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). A balance of signals derived from activating and inhibitory receptors controls the activity of NK cells (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Using the Ncr1 gfp/gfp mice, it was revealed that Ncr1 is involved in controlling influenza virus infections (5,22,25), tumor and metastases eradication (6,7,10,24), the development of type I and type II diabetes (11,23,26,27), liver fibrosis (28), and bacterial infections (3,29). In all of these studies, the activity of the Ncr1 gfp/gfp NK cells was impaired in an Ncr1-dependent manner.…”
mentioning
confidence: 99%
“…So far, evidence suggests that fusobacteria colonize adenomas or preexisting tumors rather than driving tumor initiation. [8][9][10] It will be interesting to investigate whether other tumor promoting bacteria interact with TIGIT. It also remains to be determined whether blocking the ability of fusobacteria to activate TIGIT will improve tumor control by the host's immunity.…”
Section: Prospectivementioning
confidence: 99%
“…1). 8 Thus, a bacterium-dependent, tumor immune evasion mechanism in which tumors exploit the Fap2 protein of F. nucleatum to inhibit immune cell activity via TIGIT was revealed.…”
mentioning
confidence: 99%